Complex Nasal Fractures in the Adult—A Changing Management Philosophy - Davis, Richard E.; Chu, Eugenia (Facial Plastic Surgery, 2015)
Acute management of complex nasal fractures in the adult nose is still frequently conducted using closed reduction techniques as first-line therapy. Treatment outcomes from closed reduction are often disappointing and secondary surgical corrections are required in a sizeable subset of patients. In response to the shortcomings of closed fracture manipulation, classic rhinoplasty techniques have been introduced to improve anatomic fracture reduction. Although these techniques improve the accuracy of skeletal reduction, they also weaken the nose, leaving it susceptible to the deformational forces of healing. To provide optimal anatomic fracture reduction and concomitant stabilization of the skeletal framework, we have been using contemporary strategies derived from open structure rhinoplasty and extracorporeal septal reconstruction for initial fracture treatment. Using wide-field exposure with open rhinoplasty, these strategies provide optimal fracture reduction and rigid stabilization of the septal L-strut using suture-based fixation and structural grafting techniques. The result is unsurpassed contour restoration and lasting architectural stability of the nose. When combined with power-driven instruments to cut, shape, mobilize, and create osseous suture holes, open structure stabilization of the disrupted skeletal framework establishes a new benchmark in acute fracture management.
Keywords: nasal fracture; closed reduction; open fracture stabilization; L-strut reconstruction